Job Satisfaction, Mental Symptoms, and Well-Being in Adult Workers: A Gender Analysis - M. Pilar Matud; Ligia Sánchez-Tovar; D. Estefanía Hernández-Lorenzo; David Cobos-Sanchiz (Psychiatry International, 2024)
Although studies have found that job satisfaction has an impact on workers’ physical and mental health, research has generally not focused on the psychological well-being of adult workers and a gender differential analysis has not been conducted. The aim of the current research is to determine the importance of job satisfaction for mental symptoms and well-being among adult working women and men. We also examine gender differences in job satisfaction. A non-probability sample of 1977 Spanish workers (51.6% men and 48.4% women) aged between 36 and 65 years was used in this cross-sectional study. Six questionnaires and self-report scales were used to assess the participants. For both men and women, higher job satisfaction was associated with lower depressive, somatic, anxiety, and social dysfunction symptoms; higher life satisfaction; and greater psychological well-being. Hierarchical multiple regression analyses showed that after controlling for the effects of self-esteem and social support, higher job satisfaction predicted greater life satisfaction, fewer mental symptoms, and greater psychological well-being, although the effect of job satisfaction on psychological well-being was somewhat stronger for men than for women. We conclude that job satisfaction is important for the mental health, psychological well-being, and life satisfaction of adult working women and men.